Human resource management - Martin, John, 1957- (SAGE, 2009)
John Martin presents an introduction to human resource management that will help readers to extend their understanding of key concepts and enhance their thinking skills in line with course requirements.
Keywords: personální management; personnel management; elektronické knihy; učebnice; electronic books; textbooks